2008
DOI: 10.1007/s11010-008-9896-0
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown endogenous CypA with siRNA in U2OS cells results in disruption of F-actin structure and alters tumor phenotype

Abstract: Cyclophilin A (CypA) was originally identified as a cytosolic protein possessing peptidyl-prolyl isomerase activity. CypA has been shown to play a pivotal role in the immune response, but little is known about other molecular mechanisms of CypA-mediated biologic events. In our present study, we demonstrate that knockdown CypA expression using RNAi in U2OS cells resulted in disruption of the F-actin structure, as well as decreased anchorage-independent growth, proliferation, and migration. Wild-type U2OS cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…In addition, it can also block any function of CyPA involving the area that CsA binds. As CsA is a widely used tool in research on CyPA and other cyclophilins, our results illustrate that it is a common misunderstanding that the inhibitory effect of CsA is simply viewed as the effect of blocking the PPIase activity of CyPA (39,40). In summary, our findings indicate that CyPA induces chemotaxis through a direct interaction with the ectodomain of CD147 in a PPIase-independent manner, suggesting that there exists a novel mechanism for CyPA to regulate cell signaling.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, it can also block any function of CyPA involving the area that CsA binds. As CsA is a widely used tool in research on CyPA and other cyclophilins, our results illustrate that it is a common misunderstanding that the inhibitory effect of CsA is simply viewed as the effect of blocking the PPIase activity of CyPA (39,40). In summary, our findings indicate that CyPA induces chemotaxis through a direct interaction with the ectodomain of CD147 in a PPIase-independent manner, suggesting that there exists a novel mechanism for CyPA to regulate cell signaling.…”
Section: Discussionmentioning
confidence: 54%
“…Recently Lv et al demonstrated that actin dynamism is required for AngII-induced ROS generation in VSMC 26 . Additionally, knockdown of CyPA in U2OS cells showed actin structure disorganization resulting in decreased cell migration and proliferation 22 . Previous findings from our laboratory showed that a depletion of CyPA from VSMC inhibited cell migration and proliferation 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, CyPA has been shown to be a cell cytoskeleton binding protein 19, 20 by which it can regulate neutrophil migration 21 and tumorogenesis 22 through regulating actin polymerization. The role of intracellular CyPA in AngII-induced ROS production in VSMC is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, only the ERK inhibitor PD98059 was able to decrease the activation of NF-kB and attenuate the MMP-9 activity induced by CyPA (Jin et al 2004). Moreover, previous cancer cell line studies have demonstrated that CyPA secretion is associated with cancer cell proliferation, cell cycles progression, cell invasion, and the migration and inhibition of apoptosis (Choi et al 2007;Li et al 2008;Calhoun et al 2009). Interestingly, an overexpression of CyPA is associated with resistance to chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 96%